2014
DOI: 10.1634/theoncologist.2014-0221
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Shortened Vitamin Supplementation Prior to Cisplatin–Pemetrexed Therapy for Non-Small Cell Lung Cancer

Abstract: Background. Prior supplementation with folic acid and vitamin B 12 is required to reduce pemetrexed therapy toxicity; the recommended lead-in time is at least 7 days. On the basis of previous pharmacokinetic and clinical studies, we hypothesized that the lead-in time could be shortened to 24 hours, enabling earlier commencement of standard chemotherapy; thus, we planned the first prospective trial of this regimen. Methods. Patients with advanced nonsquamous non-small cell lung cancer who had not previously rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…We observed that immediate initiation of chemotherapy and B12‐FAS was safe. This outcome was reported in previous retrospective analyses and single‐arm studies but was never verified in a randomized trial . The difference in incidence rates for any grade of cytopenia was statistically significant only for thrombocytopenia, which was more frequent in the IA.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We observed that immediate initiation of chemotherapy and B12‐FAS was safe. This outcome was reported in previous retrospective analyses and single‐arm studies but was never verified in a randomized trial . The difference in incidence rates for any grade of cytopenia was statistically significant only for thrombocytopenia, which was more frequent in the IA.…”
Section: Discussionsupporting
confidence: 58%
“…This outcome was reported in previous retrospective analyses and single-arm studies but was never verified in a randomized trial. 12,13 The difference in incidence rates for any grade of cytopenia was statistically significant only for thrombocytopenia, which was more frequent in the IA. However, the 2 groups also differed significantly at baseline for this parameter, with thrombocytopenia present in 8% of patients in the IA and in no patients in the DA at randomization.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As for the non-hematologic toxicities, fatigue was still the most common adverse reaction, 31.14% vs 30.97%, P = 0.804; because the antiemetics was routinely prophylacti-pyrimidine nucleotides, the supplements was indispensable during any chemotherapy with antagonist of folic acid [15], and vitamin B12, which involved in the manufacture of marrow erythrocyte, was also need to be supplied exogenously [16].…”
Section: Discussionmentioning
confidence: 99%
“…This letter is in reference to the study by Takagi et al in a recent issue of the journal [1]. The authors assessed total plasma homocysteine (tpHcy) concentrations at baseline in a small cohort of advanced nonsquamous non-small cell lung cancer (NSCLC) patients prior to initiation of chemotherapy (pemetrexed and cisplatin), and then correlation of toxicity profiles with baseline tpHcy levels was assessed [1].…”
mentioning
confidence: 99%